DFT study of structural, electronic, elastic and magnetic properties of In0.75Cr0.25P. (2021) - Kaur, Kirandish; Sharma, Suresh
Abstract: The theoretical calculations of structural, electronic, elastic and magnetic properties of In0.75 Cr0.25 P Diluted Magnetic Semiconductor (DMS) in Zinc Blende phase (B3) has been performed using Density Functional Theory (DFT) as implemented in the Spanish Initiative for Electronic Simulations with Thousands of Atoms (SIESTA) code with LDA + U (U = 3) exchange–correlation (XC) potential. The study of spin polarized electronic band structures and magnetic properties represents the induction of half metallic ferromagnetic behaviour in In0.75 Cr0.25 P with 100% spin polarization. Different types of elastic parameters of ternary alloy have been calculated and results confirm that this compound is stable and predicts its anisotropic and ductile nature. The hybridization of Cr-3d states with s and p states of In and P develops some local magnetic moment on non magnetic In and P atoms. The calculated results of different properties are compared with available literature data and are in good agreement.